Gender and Self-Injury in Emerging Adults - Agustina Engry; Maria Putri Prasetyo; Wynne Hariyanto; Made Dharmawan Rama Adhyatma (Psikostudia : Jurnal Psikologi, 2025)
Emerging adulthood is a life phase that is particularly vulnerable to significant psychological challenges. Mental health issues, particularly those related to self-injurious behavior, have been increasingly reported among individuals in this developmental stage. In Indonesia, gender stereotypes play a significant role in shaping how emerging adults respond to such challenges. Based on this background, it becomes essential to examine the role of gender in self-injurious behaviors among emerging adults. The participants in this study were individuals aged 18–25 years who had either engaged in or considered engaging in self-injurious behavior. A purposive sampling technique was employed, resulting in a total of 494 respondents, comprising 423 women and 71 men. The statistical analysis was conducted using the Mann–Whitney U Test. The results of the hypothesis testing indicated a p-value < 0.05 (0.035), suggesting a statistically significant difference in the tendency to engage in self-injury between male and female emerging adults. The z-score was -2.108 and the effect size (r) was 0.09, indicating a small effect size. Furthermore, women exhibited a higher frequency of several forms of self-injury, including scratching themselves, engaging in relationships where they are rejected, deliberately attempting suicide, and intentionally resigning from their jobs.Masa emerging adulthood merupakan fase kehidupan yang rentan dengan terjadinya permasalahan yang berat. Persoalan kesehatan mental, khususnya terkait perilaku self-injury saat ini ditengarai banyak dilakukan oleh emerging adult. Di Indonesia sendiri, stereotip gender menjadi faktor penting bagi emerging adult dalam merespon permasalahan sehingga dengan latar belakang tersebut, menjadi penting untuk diteliti bagaimana peran gender terkait perilaku self-injury yang dilakukan oleh emerging adult. Responden dalam penelitian adalah individu berusia 18-25 tahun dan pernah berniat melukai diri atau pernah melukai diri. Teknik pengambilan sampel menggunakan purposive sampling. Dengan metode tersebut didapatkan responden total sejumlah 494 orang yang terdiri dari 423 wanita dan 71 pria. Teknik analisis statistik yang digunakan adalah Mann-Whitney U Test. Hasil uji hipotesis menunjukkan nilai p < 0,05 (0,035) sehingga dapat disimpulkan bahwa ada perbedaan yang signifikan tingkat kecenderungan self-injury pada wanita dan pria emerging adulthood. Nilai z = -2,108 dan nilai r = 0,09 sehingga dapat disimpulkan bahwa perbedaan tingkat kecenderungan self-injury antara wanita dan pria tergolong kecil. Tingkat perbedaan frekuensi bentuk self-injury yang tinggi didominasi oleh wanita, yaitu mencakar diri sendiri, memposisikan diri dalam hubungan yang ditolak, sengaja melakukan percobaan bunuh diri, dan sengaja keluar dari pekerjaan.